Using numbers that do not count: how the latent functions of performance indicators explain their success. (June 2021) - Kempeneer, Shirley; Van Dooren, Wouter
Performance indicators have had to endure severe criticism. They are said to lack accuracy, encourage gaming and ultimately fail to improve performance. Yet, despite their well-documented weaknesses, performance indicators abound in governance. This article asks under which conditions performance indicators can improve performance outcomes, despite these proven weaknesses and dysfunctions. Our case study is the stress test of the European banking system, a high-profile performance indicator used for risk regulation. Based on interviews with risk managers in Belgian banks as well as staff at the European Central Bank, the European Banking Authority and the National Bank of Belgium, we find that the process of calculating the stress test improves performance outcomes in itself. It does so by fostering banks' capacity to self-regulate, tying into Foucault's notion of governmentality. As such, practitioners and academics should not only pay attention to how performance results can be used, but also examine how the process of calculating the performance indicator might be designed to improve performance outcomes latently.